Return to the Nation: The Organizational Challenges Confronted by Guatemalan Refugee Women - Crosby, Alison (Refuge: Canada’s Journal on Refugees, 2001)
This article focuses on the challenges faced by organized Guatemalan refugee women on return from exile in Mexico. It seems that exile provided a temporary space in which women could organize and assert their rights as women, and this space was closed down upon return to the nation. Part of the explanation can be found in conflicts over power, in particular within the return communities. It is argued that the nature of international community intervention in the camps in Mexico, and throughout the return process, may have contributed to the current community conflicts. The article highlights the new organizational strategies being created by returnee women to effectively participate at the community and national levels, and respond to the needs of their bases within the rapidly changing post–peace accord era. An initiative to create a space for dialogue and negotiation among the women’s organizations is examined.